Antimicrobial resistance of Salmonella Indiana from retail chickens in China and emergence of an mcr-1-harboring isolate with concurrent resistance to ciprofloxacin, cefotaxime, and colistin - Yujie Hu; Yujie Hu; Yingying He; Scott V. Nguyen; Scott V. Nguyen; Chang Liu; Chang Liu; Xin Gan; Wei Wang; Yinping Dong; Yinping Dong; Jin Xu; et al. (Frontiers in Microbiology, 2022)
Salmonella enterica serotype Indiana (S. Indiana) in Chinese poultry meat has aroused widespread concern because of its high prevalence and strong antimicrobial resistance. In consideration of the relationship in our previous study between S. Indiana and co-resistance to ciprofloxacin and cefotaxime (CIP-CTX), which were the first-line drug which were used in Salmonella infection in clinical, the antimicrobial resistance (AMR) of 224 CIP-CTX co-resistant S. Indiana isolated from retail chicken samples in China were investigated, with the aim of characterizing the AMR profiles and related resistance mechanisms to ciprofloxacin and cefotaxime among these CIP-CTX co-resistant S. Indiana isolates, all of which showed multi-drug-resistant (MDR) phenotypes. GyrA (S83F and D87N/G) with ParC (T57S and S80R) were the dominant amino acid substitution types, with oqxA, oqxB, and aac (6′)-Ib-cr identified as common plasmid-mediated quinolone resistance (PMQR)-encoding genes. Five blaCTX-M gene subtypes were identified with blaCTX-M-65 ranking at the top. Equally important, we obtained one isolate CFSA664 harboring the mcr-1 gene was ESBL producer with co-resistance to nine in ten classes of tested drugs inclduing colistin. A single circular chromosome and 3 circular plasmids were found in its genome. Among the 26 AMR genes identified, 24 were located on plasmid pCFSA664-1, including three ESBL genes, while plasmid pCFSA664-3 owning only the mcr-1 gene and sharing the same backbone structure with plasmids from Enterobacteriaceae. No insertion sequences were found near the mcr-1 gene but a relaxase-encoding gene in the flank, which could transfer into E. coli J53 at a relatively high frequency. S. Indiana in this study exhibited highly drug-resistant phenotypes, contributing to the acceleration of the dissemination and emergence of this pathogen among different sources. Surveillance and a One Health strategy are needed to limit the emergence of S. Indiana along the food chain.